The Prognostic Value of Lysine Acetylation Regulators in Hepatocellular Carcinoma - Sun, Liying; Zhang, Jian; Wen, Kai; Huang, Shenglan; Li, Dan; Xu, Yongkang; Wu, Jianbing (Frontiers in Molecular Biosciences, 2022)
Background: Hepatocellular carcinoma (HCC) is a tumor with high morbidity and mortality worldwide. lysine acetylation regulators (LARs) dynamically regulate Lysine acetylation modification which plays an important regulatory role in cancer. Therefore, we aimed to explore the potential clinical prognostic value of LARs in HCC. Methods: Differentially expressed LARs in normal liver and HCC tissues were obtained from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) datasets. To identify genes with prognostic value and establish the risk characteristics of LARs, consensus clustering was employed. We used univariate Cox regression survival analysis and LASSO Cox regression based on LARs to determine the independent prognostic signature of HCC. CIBERSORT and Gene Set Enrichment Analysis (GSEA) were used to estimate immune infiltration and functional enrichment analysis respectively. The expression of LAR was detected by Real-time quantitative polymerase chain reaction (RT-qPCR). statistical analyses were conducted using SPSS and R software. Results: In this study, the 33 LARs expression data and corresponding clinical information of HCC were obtained using TCGA and ICGC datasets. We found majority of the LARs were differentially expressed. Consensus cluster analysis was carried out based on the TCGA cohort, and three HCC subtypes (cluster 1, 2, and 3) were obtained. The LA3 subgroup had the worst clinical outcomes. Nine key LARs were identified to affect prognosis. The results showed that LARs signature has a strong independent prognostic value in HCC patients, whether in the training datasets or in the testing datasets. GSEA results showed that various tumor-related processes and pathways were abundant in the high-risk groups. RT-qPCR results showed that HAT1, HDAC1, HDAC2, HDAC4, and HDAC11 were highly expressed in HCC cells. Conclusion: Our results suggest that LARs play critical roles in HCC and are helpful for individual prognosis monitoring and clinical decision-making of HCC.